Suicidalidad en Adolescentes. Factores de riesgo y Modalidades de Intervención. - Carvajal, Pablo; Acevedo, Denisse; Soto, Romina; Jara, César (Cuadernos Médico Sociales, 2025)
Adolescent suicidality can be conceptualized through an addictive model where neurobiological, behavioral, and family-related factors converge. The repetition of suicide attempts, particularly among "major repeaters," resembles the relapse patterns observed in substance addictions. Key mechanisms include family dysfunction, high levels of expressed emotion, substance use, and the modulatory role of stress on neuroinflammation. Evidence highlights abnormalities in cytokines, brain-derived neurotrophic factor (BDNF), and hippocampal alterations as molecular substrates that increase vulnerability. The social and family environment acts as either a protective or risk factor, underscoring the importance of preventive interventions targeting both the individual and their context.